The Roles of the Fluorescent In Situ Hybridization (FISH) and Comparative Genomic Hybridization (CGH) Techniques in the Detection of the Breast Cancer - Harem Othman Smail (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2022)
This paper aimed to understand and compare the two popular cytogenetic techniques of fluorescence in situ hybridization (FISH) and comparative genomic hybridization (CGH) in detecting breast cancer chromosomal abnormality. Several chromosomal anomalies play a role in the development of breast cancer, and the two above approaches play an important role in confirming fluorescence in situ hybridization in particular (FISH). However, comparative genomic hybridization has developed DNA copy number profiles for most of the publicly available breast cancer cell lines for the FISH methods rely on the fluorescent probes. Chromosomal profiles can be generated for the suspected chromosomal abnormality, copy number changes between the tumour and the DNA control can be compared, and the results can be registered. Today, modern cytogenetic tools such as fluorescence in situ hybridization (FISH) are more commonly used to detect any microdeletion that cannot be detected by conventional cytogenetic karyotypes that involve a high rate of cell division and good chromosomal morphology, which pose challenges for cytogeneticists, and a long period of testing and research. Usually, this is a problem for physicians, and there are still many drawbacks and disadvantages concerning the high benefits, such as false findings. Normal chromosome in situ hybridization requires the hybridization of a labelled DNA probe into denatured chromosomal DNA present in metaphase chromosomes in an air-dried microscope slide preparation. Metaphase spreads are used for traditional chromosome FISH (metaphase FISH). Positive and positive signs of hybridization also appear as a double spot, corresponding to the hybridized probe for both sister chromatids. A further extension of chromosome painting is comparative genomic hybridization (CCI-I). CCH involves simultaneous chromosome painting in two different colours using complete DNA from two similar sources as probes, which reveal variations concerning the benefit or loss of sub-chromosomal regions or even entire chromosomes.